Optimization of Ready-Mix Concrete Quality at PT Kalla Beton - Setiawan, Preza; Indri Rahmadhani Fitriana; Lukamnul Hakim; M Gilang Indra Mardika; Michael (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2025)
Quality control from raw material to finished ready-mix concrete is vital in the construction industry, where increasing demand aligns with industry growth projected at 4% annually. PT Bumi Sarana Beton (Kalla Beton) faces challenges in maintaining consistent quality due to variations in natural raw materials, which impact product quality and cost. This research investigates the company's quality control strategies, focusing on optimizing material selection and mix designs. Experimental research methods were used, including testing different mix proportions and assessing compressive strength and production costs. The study involved aggregate suitability testing, redesigning concrete mixes with fly ash, and evaluating cost-effectiveness. Findings show that using fly ash improves compressive strength and reduces costs. The research concludes that refined material selection and mix design strategies can enhance product quality and cost efficiency. Recommendations include further exploration of alternative materials, and rigorous quality control to sustain high production standards and maintain competitive advantage in the ready-mix concrete market